2018
DOI: 10.1038/s41598-017-18839-0
|View full text |Cite
|
Sign up to set email alerts
|

The PEG-responding desiccome of the alder microsymbiont Frankia alni

Abstract: Actinorhizal plants are ecologically and economically important. Symbiosis with nitrogen-fixing bacteria allows these woody dicotyledonous plants to colonise soils under nitrogen deficiency, water-stress or other extreme conditions. However, proteins involved in xerotolerance of symbiotic microorganisms have yet to be identified. Here we characterise the polyethylene glycol (PEG)-responding desiccome from the most geographically widespread Gram-positive nitrogen-fixing plant symbiont, Frankia alni, by next-gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 85 publications
0
13
1
Order By: Relevance
“…Its proximity on some genomes of cluster 1 strains to the hybrid lectin‐kinase (FRAAL5298) is evocative of a lineage‐specific response to host polysaccharides (Pujic et al, ). A recent analysis of the response of Frankia alni cells to a PEG osmotic shock (Ghedira et al, ) has yielded a large number of upregulated proteins but few were found in the present study, suggesting the PEG response and the response to exudates are contrasted.…”
Section: Discussioncontrasting
confidence: 60%
“…Its proximity on some genomes of cluster 1 strains to the hybrid lectin‐kinase (FRAAL5298) is evocative of a lineage‐specific response to host polysaccharides (Pujic et al, ). A recent analysis of the response of Frankia alni cells to a PEG osmotic shock (Ghedira et al, ) has yielded a large number of upregulated proteins but few were found in the present study, suggesting the PEG response and the response to exudates are contrasted.…”
Section: Discussioncontrasting
confidence: 60%
“…Other in vitro proteomic studies have been done of Frankia with/without ammonium [ 22 ] or under osmotic stress [ 23 ] and have shown TCA involvement, stress determinants and various regulators.…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that the increase of the proteolytic activity could play an essential role removing damaged proteins and release amino acids that would provide osmolytes to compensate the osmotic shock. (Frees et al, 2007; Ghedira et al, 2018).…”
Section: Resultsmentioning
confidence: 99%